Effectiveness of Warm and Cold Compresses on Pain Levels Among Toddlers After Immunization in Community Health Services - Silvana Yunus; Sabirin B. Syukur; Lenny N. Ali; Indrawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Post-immunization pain is a common physiological response among toddlers caused by tissue trauma following injection procedures. This condition may lead to discomfort, prolonged crying, and increased parental anxiety, potentially affecting adherence to subsequent immunization schedules. Therefore, effective and safe non-pharmacological interventions are needed to minimize pain. This study aimed to analyze the effectiveness of warm and cold compresses on pain levels among toddlers after immunization at the Mongolato Village Integrated Health Post, Gorontalo, Indonesia. A quantitative quasi-experimental study with a two-group pretest–posttest design was conducted involving 40 toddlers selected through purposive sampling and divided into warm compress (n = 20) and cold compress (n = 20) groups. Pain levels were measured using the FLACC observation scale. Data were analyzed using the Shapiro–Wilk normality test followed by paired t-test with a significance level of 0.05. The results showed that both warm and cold compress interventions significantly reduced pain levels (p = 0.001). However, warm compress therapy demonstrated greater effectiveness, with a larger reduction in mean pain scores compared to cold compress therapy. Warm compress intervention can be recommended as an atraumatic care strategy in community-based immunization services to improve children’s comfort and support immunization program success.